The girl in his shadow : a novel - Blake, Audrey, active 2020 (Sourcebooks Landmark, 2021)
"When Dr. Croft takes in orphan Eleanor Beady, he doesn't realize that he's gained an apprentice. Raised amidst Croft's experiments, "Nora" becomes his most trusted assistant-an unthinkable and unlawful pursuit for a woman. Nora helps Croft's groundbreaking research and his clinic gain recognition, and she finds she doesn't mind working in the background, as long as she can continue to hone her skills. But the arrival of a new surgical resident threatens to undo all that Nora has strived for. Dr. Daniel Gibson is too proper to be trusted, too skilled to dismiss, and too smart to be fooled for long. He expects Nora to change her clothes before dinner and spend her evenings perfecting her needlework, not her sutures. Though Nora knows it's best not to reveal her expansive knowledge of human anatomy, she isn't going to give up the work that fascinates and fulfills her-no matter what it costs her"--